Spain bets on sustainable transitions: The RED Mechanism in 2021-2022 labor reform - Bini, Stefano (2022)
The article proposes a critical study on the specific profile of the labor reform recently introduced in the Spanish legal order: the RED Mechanism of employment flexibility and stabilization, an innovative instrument for the management of professional transitions. Furthermore, special attention is given to the key role of the formation and requalification of those persons who work.